Organizational Buying Behavior & Innovation Diffusion in solar industry: A Study on solar technology adoption by Pakistani organizations through the integration of the Organization Buying Behavior Theory and the Innovation Diffusion Theory - Ikram, Asif (2010)
Energy utilization by the world‘s population comes from several sources. However, all the energy sources humans use today can be categorized into two broad categories: renewable and non-renewable. Renewable energy is generated from natural processes that are replenished constantly (Adam et al., 2010). Renewable energy can be derived from several resources such as sun heat, deep earth heat, wind, ocean, hydropower, biomass, geothermal resources and bio fuels. On the other hand, non-renewable resources such as coal, petroleum, and gas cannot be replenished. As the world reserve of non-renewable energy depletes, it becomes imperative that the world shifts from emphasis on non-renewable energy sources to exploiting renewable resources to meet its energy demand. Several developed countries of the world have practically embarked on small to large-scale solar power systems to meet their energy demand. Solar power systems absorb the sun heat and transform that heat into electricity. Solar power systems contain several components such as solar panels, electricity storage batteries, converters (DC to AC) and wiring system. Further, solar panel contains many solar cells and each solar cell has a particular power generating capacity. Solar energy is sustainable, hence the growing interest among organizations as well as households to shift to this mode of power generation. To enhance the diffusion of this innovation, it is crucial to better understand the factors that influence adoption or intention to adopt. This research presents a theoretical and empirical model that identifies and evaluates the facilitators of solar technology adoption by Pakistani organizations through the integration of the Organization Buying Behavior Theory (OBBT) and the Innovation Diffusion Theory (IDT). The framework for this research links constructs such as environmental factors (e.g. economic outlook, government influence, and public scrutiny), organizational factors (including environmental sensitivity, organization structure, organization size, organization‘s people, and cost implication), and innovation characteristics (namely relative advantage, compatibility, complexity, and divisibility) to adoption. Since much of innovation and technology adoption research uses intention to measure adoption, this research follows this best practice in the field. To test this framework, around 150 Pakistani organizations were surveyed. The data were analyzed using multiple regression model. The results show that both OBBT and IDT are useful in understanding solar technology adoption among Pakistani organizations. More specifically, environmental factors, organizational factors and innovation characteristics each explain a considerable amount of variance in adoption. The implications of the study on theory, practice and policy-making are discussed in detail.